2016
DOI: 10.2147/rru.s96576
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the potency of a novel saw palmetto supercritical CO2 extract (SPSE) for 5α-reductase isoform II inhibition using a cell-free in vitro test system

Abstract: BackgroundThe nicotinamide adenine dinucleotide phosphate-dependent membrane protein 5α-reductase catalyses the conversion of testosterone to the most potent androgen – 5α-dihydrotestosterone. Two 5α-reductase isoenzymes are expressed in humans: type I and type II. The latter is found primarily in prostate tissue. Saw palmetto extract (SPE) has been used extensively in the treatment of lower urinary tract symptoms secondary to benign prostatic hyperplasia (BPH). The pharmacological effects of SPE include the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In another study saw palmetto whole berry and extract were demonstrated to have efficacy in influencing BPH by reducing the androgen-induced prostate enlargement [22]. Recently, Pais et al reported the 5-α reductase inhibitory potential of saw palmetto supercritical CO 2 extract using a cell-free in vitro test system [23]. The present study was conducted to evaluate the efficacy of VISPO, a novel supercritical CO 2 extract of saw palmetto fruits with higher β-sitosterol content (3%).…”
Section: Introductionmentioning
confidence: 99%
“…In another study saw palmetto whole berry and extract were demonstrated to have efficacy in influencing BPH by reducing the androgen-induced prostate enlargement [22]. Recently, Pais et al reported the 5-α reductase inhibitory potential of saw palmetto supercritical CO 2 extract using a cell-free in vitro test system [23]. The present study was conducted to evaluate the efficacy of VISPO, a novel supercritical CO 2 extract of saw palmetto fruits with higher β-sitosterol content (3%).…”
Section: Introductionmentioning
confidence: 99%